Preparation method and application of oxygen vacancy-containing bismuth vanadate or metal bismuth-loaded bismuth vanadate

By using bismuth vanadate BiVO4-OVs with oxygen-containing vacancies or bismuth vanadate xBi0/BiVO4 supported by metal bismuth as catalysts, catalyzing oxygen oxidation of cinnamaldehyde under light, solving the problems of low yield and poor naturalness in the prior art, and achieving efficient and green benzaldehyde preparation.

CN119701926APending Publication Date: 2025-03-28GUANGXI UNIV

Patent Information

Application Number
CN202510044036.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-10
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

In the preparation of natural benzaldehyde, the reaction conditions are harsh and the equipment requirements are high. The yield of benzaldehyde is low and the naturalness is poor, making it difficult to reach the industrialization level.

Method used

Benzaldehyde is prepared by catalyzing oxygen oxidation of cinnamaldehyde under light conditions using bismuth vanadate BiVO4-OVs or bismuth supported bismuth vanadate xBi0/BiVO4 under light conditions.

Benefits of technology

The utilization rate of cinnamaldehyde is improved, efficient oxidation is achieved, the selectivity and yield of benzaldehyde are significantly improved, and the catalyst has no effect on the naturalness of benzaldehyde.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701926A_ABST
    Figure CN119701926A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method of oxygen vacancy-containing bismuth vanadate BiVO4-OVs or metal bismuth-loaded bismuth vanadate xBi0 / BiVO4. The preparation method comprises the following steps: weighing bismuth nitrate pentahydrate and ammonium metavanadate according to a molar ratio of bismuth nitrate pentahydrate to ammonium metavanadate of 1: 1 + x; the preparation method comprises the following steps: respectively dissolving bismuth nitrate pentahydrate and ammonium metavanadate in a solvent, fully mixing the bismuth nitrate pentahydrate and the ammonium metavanadate, adjusting the pH value of the solution, placing a reaction system in an environment of 140-180 DEG C for reaction, washing and drying a product, and roasting under the protection of argon to obtain the product. In addition, the invention also discloses an application of the bismuth vanadate BiVO4-OVs containing oxygen vacancies or the bismuth vanadate xBi0 / BiVO4 loaded with metal bismuth as a catalyst in preparation of benzaldehyde by photocatalytic oxygen oxidation of cinnamyl aldehyde. According to the method, the utilization rate of cinnamyl aldehyde can be increased, efficient oxidation can be achieved in the initial stage of reaction, good benzaldehyde selectivity can be achieved, and the adopted catalyst is efficient and non-toxic and has no influence on the naturalness of benzaldehyde.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of forest chemical product processing, and specifically relates to a preparation method and application of bismuth vanadate containing oxygen vacancies or bismuth vanadate loaded with metal bismuth. Background Art

[0002] Benzaldehyde, also known as benzoinaldehyde, has a special bitter almond smell. Natural benzaldehyde is often found in essential oils such as bitter almond oil, hyacinth oil, patchouli oil and ylang-ylang oil, and is also mainly found in leaves, seeds or stem barks of plants in the form of glycosides. At the same time, benzaldehyde is also an important organic intermediate that can be used in industries such as medicine, pesticides, and spices. The main component of cinnamon oil is cinnamaldehyde, with a content of more than 70%. Cinnamon oil or cinnamaldehyde can be used as a raw material for preparing natural benzaldehyde. At present, the main method for producing natural benzaldehyde in China is the alkaline hydrolysis of cinnamaldehyde, but because it is a two-phase reaction, it is difficult for the reactants to fully contact each other, resulting in a low yield of benzaldehyde. Therefore, many researchers have made many improvements to the alkaline hydrolysis method to improve the yield of benzaldehyde. For example, domestic patents (CN1446789A, CN1749231A, CN1911891A, CN101985414A) have improved the production equipment of this method, reducing costs, and improving quality and yield to varying degrees, but the benzaldehyde yield has not yet reached the industrial level, and the impurity content is relatively high. Domestic patents (CN1179934C, CN1634837A) and US patents (US4683342, US4617419) introduce phase transfer catalysts or surfactants to increase the solubility of cinnamaldehyde in water, but both of the above additives are not conducive to maintaining the naturalness of benzaldehyde. Gao Fei et al. (Journal of Chemical Engineering of Colleges and Universities, 2006, 20 (4): 544-547) proposed to synthesize benzaldehyde in near-critical water, but the reaction conditions are harsh, the equipment requirements are high, and the naturalness of benzaldehyde will also be reduced. In order to solve these problems, exploring other ways to prepare benzaldehyde is an important direction of current research.

[0003] The photocatalytic technology using light energy to selectively oxidize cinnamaldehyde to benzaldehyde is a greener and milder reaction pathway than chemical energy and thermal energy. Liu Zili et al. used graphite phase carbon nitride composite materials and NHPI to synergistically photocatalytically oxidize toluene to prepare benzaldehyde (CN114950518B), but the reaction required toxic additives, and the substrate was toluene, and the obtained benzaldehyde was not natural. Yang Xiaojing et al. prepared bismuth molybdate crystals containing oxygen vacancies for photocatalytic oxygen oxidation of benzyl alcohol to prepare benzaldehyde. The obtained benzaldehyde selectivity was as high as 99%, but the solvent used was the toxic substance trifluorotoluene. Therefore, there is still a lot of room for improvement to achieve photocatalytic oxygen oxidation of cinnamaldehyde under mild conditions. Summary of the invention

[0004] In order to overcome the deficiencies of the prior art, the present invention provides a method for preparing benzaldehyde by photocatalytic oxygen oxidation of cinnamaldehyde.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] Bismuth vanadate BiVO4-OVs containing oxygen vacancies or bismuth vanadate xBi loaded with metal bismuth 0 / BiVO4 preparation method, comprising the following steps: Step 1: weighing bismuth nitrate pentahydrate and ammonium metavanadate according to the molar ratio of bismuth nitrate pentahydrate to ammonium metavanadate of 1:1+x, wherein 0≤x≤0.8; Step 2: dissolving the bismuth nitrate pentahydrate weighed in Step 1 in solvent A, the solution is recorded as solution A; Step 3: dissolving the ammonium metavanadate weighed in Step 1 in solvent B, the solution is recorded as solution B; Step 4: fully mixing solution A and solution B, adjusting the pH of the solution to 6-8, and continuing to stir Mix well; Step 5: Pour into the polytetrafluoroethylene lining of the autoclave, place the autoclave in an environment of 140-180°C, and keep warm for 6-24 hours; Step 6: Filter out the product, then wash and dry; Step 7: Calcine the dried product at 350-600°C under argon protection for 2-6 hours to obtain the product. When x=0 in Step 1, the product is bismuth vanadate BiVO4-OVs containing oxygen vacancies; when x>0 in Step 1, the product is bismuth vanadate xBi supported by metal bismuth 0 / BiVO4.

[0007] Further, in Step 2, the mass volume ratio of bismuth nitrate pentahydrate to the solvent in solution A is w / v=1-5%, and the solvent A for dissolving bismuth nitrate pentahydrate is ethylene glycol; in Step 3, the mass volume ratio of ammonium metavanadate to the solvent in solution B is w / v=1-5%, and the solvent B for dissolving ammonium metavanadate is deionized water. Further, in Step 4, the pH is adjusted by adding ammonia water. Further, in Step 6, the mixture is washed three times with anhydrous ethanol and deionized water respectively, and then placed in a vacuum drying oven and kept warm at 40-80°C for 6-24h.

[0008] A method for preparing benzaldehyde, using cinnamaldehyde as a raw material, and using bismuth vanadate BiVO4-OVs containing oxygen vacancies or bismuth vanadate xBi supported by metal bismuth 0 / BiVO4 is used as a catalyst to catalyze the oxidation of cinnamaldehyde by oxygen under light conditions.

[0009] Furthermore, the catalyst is added at 1.5-7.5% of the mass of cinnamaldehyde. Furthermore, cinnamaldehyde is dissolved in a solvent at a molar volume concentration of 0.1-1 mol / L. Furthermore, the solvent is acetonitrile, alcohol, ether, benzene or chloroform. Furthermore, the illumination condition is a xenon lamp irradiation light power density of 200-600 mw / cm 2 The photocatalytic reaction time is 2 to 12 hours.

[0010] The bismuth vanadate BiVO4-OVs containing oxygen vacancies or the bismuth vanadate xBi supported by metal bismuth 0 Application of BiVO4 as catalyst in photocatalytic oxygen oxidation of cinnamaldehyde to prepare benzaldehyde.

[0011] Preferably, in Step 1, 0.2≤x≤0.8, 0.4≤x≤0.7, 0.5≤x≤0.6 or 0.5≤x≤0.65.

[0012] The xBi 0 / BiVO4, x represents the excess ratio of ammonium metavanadate to bismuth nitrate pentahydrate in terms of the amount of substance during preparation. In Step 1, when x=0, the reaction is carried out according to a molar ratio of bismuth nitrate pentahydrate to ammonium metavanadate of 1:1, and then the bismuth vanadate is calcined in Step 7 to form oxygen vacancies. The obtained product is bismuth vanadate containing oxygen vacancies, represented by the code BiVO4-OVs. In this case, the product has no metallic bismuth loading. In Step 1, when x>0, the ammonium metavanadate is in excess, and then the product is calcined in Step 7 to form bismuth vanadate loaded with metallic bismuth, represented by the code xBi 0 In the case that ammonium metavanadate is not excessive in Step 1, if the calcination in Step 7 is not performed, the obtained product is ordinary bismuth vanadate, which can be recorded as BiVO4-Ar-0h.

[0013] Compared with the prior art, the present invention has the following beneficial effects:

[0014] The xBi used in the present invention 0 / BiVO4 catalyst has the characteristics of "double function", which not only reflects its characteristics as a photosensitizer, performs efficient energy transfer, and can produce more singlet oxygen that is conducive to oxidation; it also reflects its characteristics as a photocatalyst, quickly generates photogenerated carriers, and provides active intermediates for substrate conversion. Therefore, the present invention can improve the utilization rate of cinnamaldehyde, achieve efficient oxidation at the initial stage of the reaction, and achieve good benzaldehyde selectivity. The xBi used in the present invention 0 / BiVO4 catalyst is highly efficient and non-toxic, and has no effect on the naturalness of benzaldehyde. The process device of the invention is novel, the operation is simple, the reaction process is green, the prepared benzaldehyde has high purity, and has certain development potential and industrial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0015] Figure 1 These are the activity test results of photocatalytic cinnamaldehyde oxidation of catalysts prepared under different pH conditions.

[0016] Figure 2 These are the activity test results of photocatalytic cinnamaldehyde oxidation of catalysts prepared under different temperature conditions.

[0017] Figure 3 These are the activity test results of photocatalytic cinnamaldehyde oxidation of catalysts prepared with different calcination times.

[0018] Figure 4 XRD patterns of BiVO4-Ar-0h and BiVO4-Ar-2h and the XRD pattern of the monoclinic BiVO4 standard card.

[0019] Figure 5 Full XPS spectra of BiVO4-Ar-0h and BiVO4-Ar-2h (a) and XPS spectra of Bi 4f (b), V 2p (c) and O1s (d).

[0020] Figure 6 N2- adsorption-desorption isotherms (a) and pore size distribution diagram (b) of BiVO4-Ar-0h and BiVO4-Ar-2h.

[0021] Figure 7 The BiVO4 unit cell model (a) and the BiVO4 (001) perfect crystal plane (b).

[0022] Figure 8 Perfect BiVO4(001) crystal plane (a) and BiVO4(001) crystal plane containing oxygen vacancies (b).

[0023] Fig. 9 (a) The two-dimensional color-filled cross-section diagram and (c) the three-dimensional isosurface diagram of the charge difference density of oxygen on the BiVO4 (001) crystal plane, (b) The two-dimensional color-filled cross-section diagram and (d) the three-dimensional isosurface diagram of the charge difference density of cinnamaldehyde molecules on the BiVO4 (001) crystal plane.

[0024] Fig.10 These are the experimental results of capturing active oxygen species in the photocatalytic oxygen oxidation of cinnamaldehyde to benzaldehyde by BiVO4-Ar-2h.

[0025] Fig.11 This is the possible reaction pathway for the photocatalytic oxygen oxidation of cinnamaldehyde by BiVO4-Ar-2h.

[0026] Fig.12The possible mechanism of photocatalytic oxygen oxidation of cinnamaldehyde to prepare benzaldehyde by BiVO4-Ar-2h.

[0027] Fig.13 BiVO4-Ar-2h and xBi 0 / BiVO4 XRD spectrum (a) and its local enlarged image (b).

[0028] Fig.14 BiVO4-Ar-2h and xBi 0 Infrared spectrum of / BiVO4.

[0029] Fig.15 BiVO4-Ar-2h and 0.6Bi 0 XPS spectra of BiVO4: Bi 4f(a) and enlarged Bi 0 Bi 4f(b); V2p(c); O 1s(d).

[0030] Fig.16 0.6Bi 0 TEM images (a and b) and EDS images (c) of / BiVO4.

[0031] Fig.17 is BiVO4-Ar-2h(a),0.2Bi 0 / BiVO4(b),0.4Bi 0 / BiVO4(c),0.6Bi 0 / BiVO4(d) and 0.8Bi 0 / BiVO4(e) SEM image.

[0032] Fig.18 BiVO4-Ar-2h and xBi 0 N2- adsorption-desorption isotherms (a) and pore size distribution diagram (b) of / BiVO4.

[0033] Fig.19 BiVO4-Ar-2h and xBi 0 UV-visible diffuse reflectance spectrum (a) and band gap energy spectrum (b), XPS valence band spectrum (c) and energy spectrum arrangement (d) of / BiVO4.

[0034] Fig. 20 BiVO4-Ar-2h and xBi 0 Transient photocurrent response (a) and EIS Nyquist plot (b) of / BiVO4.

[0035] Fig.21 xBi 0Cinnamaldehyde conversion rate (a), benzaldehyde selectivity (b) and benzaldehyde yield (c) of cinnamaldehyde by photocatalytic oxidation of cinnamaldehyde by / BiVO4.

[0036] Fig. 22 After the reaction, 0.6Bi 0 / BiVO4 SEM image.

[0037] Fig.23 0.6Bi 0 / BiVO4 cycle stability experiment.

[0038] Fig.24 0.6Bi 0 XRD spectra (a) and FT-IR spectra (b) of / BiVO4 before and after 5 cycles of reaction.

[0039] Fig.25 BiVO4-Ar-2h and xBi 0 / TEMP- of BiVO4 1 O2(a) and DMPO-·O2 – (b) ESR diagram.

[0040] Fig.26 is the reaction of BiVO4-Ar-2h and xBi with p-benzoquinone (ac) and furfuryl alcohol (df) as quenchers 0 Cinnamaldehyde conversion (a, d), benzaldehyde selectivity (b, e) and benzaldehyde yield (c, f) of cinnamaldehyde catalyzed oxidation by / BiVO4.

[0041] Fig. 27 BiVO4-Ar-2h and xBi 0 O2-TPD diagram of / BiVO4.

[0042] Fig.28 xBi 0 Mechanism of photocatalytic oxygen oxidation of cinnamaldehyde by BiVO4.

[0043] The English meanings involved in the accompanying drawings are as follows: Conversion of cinnamaldehyde; Selectivity of benzaldehyde; Yield of benzaldehyde; pH value of hydrothermal; Hydrothermal temperature; Calcination time; Intensity; Binding Energy; Relative pressure; Pore Diameter; dV / dD Pore Volume; Volume adsorpted; Quencher; Percent; Cleavage; Hydrolyzation; Isomerisation; Rearrangement; Wavenumber; Transmittance; Wavelength; Current Density; Percentage; Magnetic Field; photosensitizer; Fast; photogenerated electrons photogenerated electrons; Long-lasting; cinnamaldehyde cinnamaldehyde; benzaldehyde benzaldehyde. DETAILED DESCRIPTION

[0044] The catalyst characterization methods involved in each embodiment are as follows:

[0045] (1) The crystal composition of the catalyst was analyzed by X-ray diffraction (XRD). Cu Ka was used as the radiation source, the scanning speed was 10° / min, and the test was carried out on a Bruker D8 X-ray diffractometer goniometer with a test range of 10-90°. (2) The elemental composition and valence state of the sample surface were analyzed by X-ray photoelectron spectroscopy (XPS). The test was carried out on a Thermo Scientific K-Alpha instrument in the United States, the excitation source was Al Kα rays (hν=1486.6eV), the beam spot was 400um, and the vacuum degree of the analysis chamber was better than 5.0E –7mBar. (3) The specific surface area and pore structure of the sample were studied by nitrogen adsorption and desorption test. First, the sample was pretreated at 120°C in a vacuum environment for 12 hours, and then tested on a TristarⅡ (Mike Instruments, USA) physical adsorption instrument. The Brunauer-Emmett-Teller (BET) equation was used to calculate the specific surface area of ​​the sample, and the Barrett-Joyner-Halenda (BJH) was used to obtain the pore structure information of the sample. (4) The surface group and chemical bond information of the catalyst were analyzed by Fourier transform infrared spectroscopy (FT-IR). The test was performed on a Bruker TENSORⅡ infrared spectrometer. The test range is 400-4000cm –1 , with white KBr as the background. (5) The morphology and size of the catalyst sample were observed by scanning electron microscopy (SEM). During the test, a small amount of sample was directly adhered to the conductive glue, and gold was sprayed for 45 seconds using a Quorum SC 7620 sputtering coater with a gold spraying current of 10 mA. The sample was then photographed on a German Zeiss Gemini SEM 300 instrument with an acceleration voltage of 3 kV. (6) The morphology and energy spectrum (EDS) of the catalyst were analyzed by transmission electron microscopy (TEM). During the test, the sample was dispersed in an ethanol solution and ultrasonicated, and then the dispersed solution was dripped onto a copper mesh. After drying, the sample was photographed on a Japanese JEOL JEM-F200 instrument with an acceleration voltage of 200 kV. (7) The absorption edge, bandgap width and light absorption performance of the catalyst were analyzed by ultraviolet-visible diffuse reflectance absorption spectroscopy (UV-Vis DRS). The test was conducted on a TU-1901 UV-visible spectrophotometer (Beijing Spectroscopy General Instrument Co., Ltd.), using BaSO4 as a reference. (8) The O2 – and 1 In ESR detection, DMPO and TEMP are used as O2 – and 1 The spectrometer is equipped with a 300W xenon lamp as the irradiation source. The central field of the electron spin resonance spectrometer is 3510.00G, the microwave frequency is 9.85GHz, and the power is 6.32mW.

[0046] Example 1

[0047] 1.1 Preparation method of bismuth vanadate (BiVO4-OVs) catalyst containing oxygen vacancies

[0048] (S1) Dissolve 2.43g (0.005mol) of bismuth nitrate pentahydrate in a 100mL beaker containing 30mL of ethylene glycol, and the solution is recorded as A. (S2) Dissolve 0.58g (0.005mol) of ammonium metavanadate in a 100mL beaker containing 30mL of deionized water, and the solution is recorded as B. (S3) Slowly drip solution B into solution A while stirring with a magnetic stirrer, and then stir and mix thoroughly for 30min, with the speed of the magnetic stirrer being 500rpm / min. (S4) Then add ammonia water with a mass fraction of 25.0-28.0% dropwise to adjust the pH of the solution (4, 7 and 10), continue stirring for 1h, pour the suspension into the polytetrafluoroethylene liner of a 100mL high-pressure reactor, heat it to a certain temperature (140, 160, 180℃) in an oven, and keep it warm for 8h. (S5) The obtained sample was washed three times with 40 mL of anhydrous ethanol and deionized water respectively, then placed in a vacuum drying oven and kept at 60°C for 10 h to obtain an uncalcined sample, which was recorded as BiVO4-Ar-0h. (S6) BiVO4-Ar-0h was placed in a tube furnace and heated to 450°C at a heating rate of 5°C / min, and kept warm for 2, 4, and 6 h, respectively. The obtained samples were recorded as BiVO4-Ar-2h, BiVO4-Ar-4h, and BiVO4-Ar-6h. BiVO4 containing oxygen vacancies is represented by BiVO4-OVs, including BiVO4-Ar-2h, BiVO4-Ar-4h, and BiVO4-Ar-6h.

[0049] 1.2 Effect of preparation conditions on the photocatalytic activity of BiVO4-OVs in the oxidation of cinnamaldehyde by oxygen

[0050] The catalysts obtained from different single factor experiments were used to perform activity tests, and the remaining steps were the same as those in Section 2.1 of Example 2.

[0051] 1.2.1 pH of the precursor solution

[0052] The photocatalytic performance of BiVO4-OVs prepared from precursor solutions at pH 4, 7 and 10 was investigated. The hydrothermal temperature was 160°C and the tube furnace was calcined for 2 h. The activity results are shown in Figure 1 .

[0053] from Figure 1It can be seen that when no catalyst is added, the conversion rate of cinnamaldehyde, the selectivity of benzaldehyde and the yield of benzaldehyde are 28.4%, 43.5% and 12.4% respectively. When the catalyst is used, whether it is the conversion rate of cinnamaldehyde, the yield of benzaldehyde, or the selectivity of benzaldehyde, it has been improved to a certain extent compared with not adding a catalyst, indicating that BiVO4-OVs has an effective photocatalytic effect on the reaction. By comparing the BiVO4-OVs photocatalysts prepared under different acidic and alkaline conditions, it can be seen from the activity test results that the catalyst obtained under neutral conditions (pH = 7) is more conducive to catalyzing the oxidation of cinnamaldehyde. After ten hours of reaction, the conversion rate of cinnamaldehyde, the selectivity of benzaldehyde and the yield of benzaldehyde reached 47.1%, 58.4% and 27.5% respectively. The BiVO4-OVs prepared under acidic conditions are mainly tetragonal zircon-type crystal phases, while neutral conditions are conducive to the formation of high-crystallinity monoclinic BiVO4-OVs. Under alkaline conditions, the monoclinic crystallinity is weakened, and Bi(OH)3 may even be generated. Combined with the activity data, it is shown that the monoclinic BiVO4-OVs is more conducive to catalyzing the conversion of cinnamaldehyde.

[0054] 1.2.2 Precursor hydrothermal temperature

[0055] The influence of hydrothermal temperature cannot be ignored. By adjusting the hydrothermal temperature of the precursor during the preparation process, the optimal preparation temperature was screened out in order to obtain the BiVO4-OVs photocatalyst with the best activity and the most stable structure. To this end, the preparation was carried out at hydrothermal temperatures of 140, 160 and 180 ° C, respectively, and the tube furnace was calcined for 2 hours. The pH of the precursor solution was 7, and it was used for the activity test of photocatalytic oxygen oxidation of cinnamaldehyde. The activity test results are shown in Figure 2. Figure 2 shown.

[0056] Depend on Figure 2 It can be seen that the activity order of the catalysts prepared at these three temperatures is: 160℃>140℃>180℃. Within a certain temperature range, increasing or decreasing the temperature in a small range does not have much effect on the activity. If the preparation temperature is low, the crystal growth may be insufficient and the crystallization may not be ideal, resulting in unsatisfactory activity. If the preparation temperature is too high, carbon deposits are easily formed on the surface of the catalyst, reducing the available surface area and causing activity decay. At the same time, higher temperatures will cause the active component grains to grow, the specific surface area to decrease, and the activity to decrease. The appropriate preparation temperature can induce the growth of BiVO4-OVs photocatalysts with good crystallinity and high stability. Therefore, 160℃ is adopted as the preparation temperature of BiVO4-OVs.

[0057] 1.2.3 Roasting time

[0058] Although BiVO4 has a significant photocatalytic promoting effect on cinnamaldehyde, its photocatalytic efficiency needs to be further improved. Oxygen vacancies, as a crystal defect, can increase the charge carrier density inside the crystal, promote the separation of body charge and surface charge, and accelerate the interfacial charge transfer. Therefore, the present invention further constructs oxygen vacancies for BiVO4 crystals through a mild calcination treatment to improve its photocatalytic oxidation performance of cinnamaldehyde. The calcined precursor is prepared under the conditions of pH 7 and hydrothermal temperature of 160°C as discussed above, and then calcined at 450°C in a tubular furnace for 2, 4, and 6h, respectively, to obtain the final catalysts BiVO4-Ar-2h, BiVO4-Ar-4h, and BiVO4-Ar-6h. The uncalcined BiVO4 precursor is BiVO4-Ar-0h. The activity test results are as follows Figure 3 shown.

[0059] Depend on Figure 3 It can be seen that the catalytic activity of BiVO4 after calcination has been improved to a certain extent. After BiVO4-Ar-2h was calcined for 2h, it was used to catalyze the oxidation of cinnamaldehyde for 10h, and the conversion rate of cinnamaldehyde, benzaldehyde selectivity and benzaldehyde yield reached 60.2%, 60.3% and 36.3% respectively. The conversion rate of cinnamaldehyde and the yield of benzaldehyde were both increased by about 10%. However, when the calcination time was further extended, the selectivity of benzaldehyde remained almost unchanged, and the conversion rate of cinnamaldehyde was only increased by 3%-4%. Considering the reduction of energy dissipation, the catalyst prepared with a calcination time of 2h is the best.

[0060] Therefore, in summary, the optimal preparation conditions are a hydrothermal pH value of 7, a hydrothermal temperature of 160°C, and finally calcination in a tubular furnace for 2 hours. The resulting catalyst has a better catalytic effect and lower energy consumption under the preparation conditions.

[0061] 1.3 Characterization and analysis using BiVO4-Ar-2h as an example and BiVO4-Ar-0h as a comparison

[0062] 1.3.1 Analysis of XRD results

[0063] The crystal structure of BiVO4-Ar-2h after heat treatment in Ar atmosphere was analyzed by X-ray diffraction (XRD) and compared with the XRD spectrum of BiVO4-Ar-0h prepared by direct hydrothermal treatment. Figure 4 shown.

[0064] Depend on Figure 4It can be seen that both samples have obvious characteristic peaks at 2θ=18.68, 19, 28.60, 28.82, 28.97, 30.35, 34.51, 35.24°, etc., which correspond to the (101), (011), (103), (013), (112), (004), (200), (020) planes on the standard card of monoclinic BiVO4 (JCPDS#83-1699). This shows that the monoclinic BiVO4 photocatalyst was successfully prepared in this experiment, and the introduction of oxygen vacancies will not change the crystal structure of BiVO4. Moreover, the characteristic peaks of the two samples did not shift relative to the standard card, nor did they appear to be missing or increased. The main characteristic peaks are very sharp, indicating that the crystallinity of the catalysts is good and free of impurities. After heating treatment, the strength of the (004) crystal plane of BiVO4-Ar-2h increases, which may be due to the construction of oxygen vacancies while also improving the exposure of the (004) crystal plane.

[0065] 1.3.2 Analysis of XPS measurement results

[0066] The chemical composition and local electronic environment of BiVO4-Ar-0h and BiVO4-Ar-2h samples were analyzed by XPS.

[0067] Figure 5 The total scan spectrum shown in a shows the presence of O, V, Bi, and C elements in BiVO4. The binding energy results were adjusted according to the C–C binding energy of C1s, 284.8 eV. Figure 5 b shows the Bi 4f of BiVO4 7 / 2 and Bi 4f 5 / 2 The binding energies of Bi 3+ Characteristic peaks of ions. Figure 5 In the XPS spectrum of V 2p shown in c, the peak at 516.6 eV corresponds to V 5+ V 2p 3 / 2 , 524.1eV corresponds to V 5+ 2p 3 / 2 and V 2p 1 / 2 The Bi 4f and V 2p characteristic peaks of bismuth vanadate did not change significantly before and after calcination. Figure 5 The O1s peak at about 530 eV shown in d is split into its component peaks. The component peaks at 529.7, 531.1 and 533.5 eV are respectively attributed to lattice oxygen (O latt ), oxygen vacancies (OVs) and adsorbed oxygen on the sample surface (O ads ).

[0068] The results show that after calcination in an Ar atmosphere, the most obvious change in bismuth vanadate is that the characteristic peak representing oxygen vacancies in the O1s peak diagram has been significantly enhanced, and the intensity of oxygen adsorption has also been improved. This shows that the preparation process increases the oxygen vacancy content of the catalyst, which is also conducive to the adsorption of oxygen.

[0069] 1.3.3 Analysis of specific surface area and average pore size measurement results

[0070] The specific surface area and average pore size distribution of BiVO4-Ar-0h and BiVO4-Ar-2h were determined by nitrogen adsorption and desorption experiments. The specific surface area of ​​BiVO4-Ar-0h and BiVO4-Ar-2h samples was studied by Brunauer-Emmett-Teller (BET) method, and the pore size distribution of samples was studied by Barrett-Joyner-Halenda (BJH) method. The results are shown in Figure 2. Figure 6 shown.

[0071] Depend on Figure 6 It can be seen that the nitrogen isothermal adsorption-desorption curve shows typical IV type isotherm characteristics, which means that there is a mesoporous structure in the material. In addition, the curve rises significantly in the area with high relative pressure (close to 1), which may indicate that there is also a macroporous structure in the material. The presence of mesopores and macropores facilitates the diffusion of reactant molecules and the transmission of photogenerated carriers. The pore size distribution data calculated according to the BJH formula is plotted as follows Figure 6 The curve shown in b shows the change in the pore size of the semiconductor catalyst. In the pore size distribution curve of BiVO4-Ar-2h, it can be seen that its corresponding curve is smoother and has fewer impurity peaks, indicating that its pore size and distribution are more uniform, which helps to provide a larger specific surface area and more active sites, thereby possibly enhancing its photocatalytic performance.

[0072] From the data in Table 1, it can be seen that after calcination in an argon atmosphere, the specific surface area of ​​BiVO4-Ar-2h is 1.35 cm 2 / g, compared with BiVO4-Ar-0h (0.53cm 2 / g) has increased. The larger specific surface area can provide more active sites for the reaction.

[0073] Table 1 Specific surface area and average pore size distribution of BiVO4-Ar-0h and BiVO4-Ar-2h

[0074]

[0075] The above research shows that the improvement of the photocatalytic performance of the BiVO4-Ar-2h photocatalyst can be attributed to the fact that after the catalyst is calcined, oxygen vacancies are generated in the catalyst, the surface structure changes, the specific surface area increases, and the active sites increase, which is more conducive to the adsorption and activation of the substrate, thereby effectively improving the photocatalytic ability.

[0076] Example 2

[0077] 2.1 Test steps for the activity and stability of photocatalysts for the photocatalytic oxidation of cinnamaldehyde by oxygen

[0078] The performance test of photocatalyst photocatalytic oxygen oxidation of cinnamaldehyde was carried out in a quartz reactor. The specific operation steps are as follows: 30 mg of photocatalyst was dispersed in a mixed solution containing 0.66 g (0.005 mol) cinnamaldehyde and 10 mL acetonitrile, and ultrasonic treatment was performed for 10 min. Before illumination, the photocatalytic reaction system was purged with O2 for 10 min to exclude air as much as possible. Then, a rubber ball with a volume of 1 L was used to collect oxygen as the oxygen source for subsequent reactions. The prepared reaction system was magnetically stirred for 30 min in a dark environment, and a 300 W xenon lamp was used to irradiate from the top after the system reached adsorption and desorption equilibrium. The suspension was continuously stirred during the reaction of photocatalytic oxidation of cinnamaldehyde, and the reactor temperature was maintained at 25 ° C by circulating cooling water. Samples were taken every 2 h of the reaction, and the catalyst was filtered to remove the catalyst, and the reaction was carried out for 10 h.

[0079] 2.2GC detection of reaction products

[0080] Weigh 0.2 g of the reaction solution filtered through the organic filter head and add it into a 10 mL volumetric flask to a concentration of 2 g·L –1 Take nitrobenzene as the internal standard, accurately measure 1 mL and add acetonitrile to the scale in a volumetric flask, shake well and take 0.2 μL with a chromatographic needle and inject into the gas chromatograph for quantitative analysis.

[0081] The gas chromatography test conditions are as follows: the column used for chromatography is a 30m×0.25mm SE-54 gas chromatography column, an FID detector is used, and high-purity N2 is used as the chromatographic carrier gas with a flow rate of 40mL·min –1 In the method file, the column oven temperature is 160°C, the vaporizer temperature is 260°C, and the flame ionization detector (FID) temperature is 260°C. After the temperature program is ready, 400 mL min –1 of air and 40 mL min –1 of hydrogen, with the split ratio set to 15:1.

[0082] The internal standard method was used to calculate and analyze the concentration of each substance in the product after the reaction. According to the peak area ratio of the reactant and the internal standard, the concentration of each component in the reaction solution was calculated using the internal standard working curve. The cinnamaldehyde conversion rate, benzaldehyde selectivity and benzaldehyde yield were calculated using formulas (2-1)-(2-3).

[0083]

[0084] Product yield (%) = corresponding product selectivity × cinnamaldehyde conversion rate (0-2)

[0085] 2.3 GC-MS detection of reaction products

[0086] In the oxidation process of cinnamaldehyde, in addition to the main product benzaldehyde, a large number of by-products are also generated. However, only some known characteristic peaks of simple compounds can be detected by gas chromatography, and due to the limitations of gas chromatography detectors, there are still a considerable number of products that cannot be detected in GC. Therefore, it is necessary to use gas chromatography-mass spectrometry (GC-MS) combined with a certain amount of database to detect the substances present in the cinnamaldehyde reaction system before and after the reaction. Using BiVO4-Ar-2h as the catalyst, the reaction was carried out according to the steps in 2.1, and the reaction solution after thorough reaction was subjected to GC-MS detection. Weigh 0.2g of the reaction solution filtered by an organic filter head and add it to a 10mL volumetric flask at a concentration of 2g·L –1 1 mL of nitrobenzene was used as the internal standard. After accurately measuring 1 mL, acetonitrile was added to the volumetric flask to the mark. After shaking, the mixture was qualitatively analyzed by gas chromatography-mass spectrometry. The GC-MS detection conditions were as follows: SH-Rxi-5Si MS (30m×0.25mm×0.25μm) capillary column was used; column temperature program: starting temperature 50℃, increased to 100℃ at 5℃ / min, maintained for 1min, then increased to 200℃ at 10℃ / min, maintained for 10min; injection port temperature: 230℃; carrier gas: high-purity helium; column flow rate: 1.69mL / min; injection mode: split injection, split ratio 30:1; injection volume: 1.0μL. Transfer line temperature: 250℃, ion source temperature: 200℃, solvent delay: 2min; acquisition mode: full scan mode (Scan), mass acquisition range: 35–500m / z; multiplier voltage: reference tuning conditions. Mass spectrometry data were retrieved from the NIST database (NIST08, NIST14, NIST21, NIST107).

[0087] The analysis results are listed in Table 2. It can be seen from the analysis results that after oxidation, a total of 10 detection signals were obtained from the system. In addition to cinnamaldehyde, the oxidation products of cinnamaldehyde>C=C< double bond and C=O double bond were also obtained, as well as the by-products of deep oxidation. Among them, the characteristic peak area of ​​benzaldehyde is the largest, which is consistent with the gas phase detection results.

[0088] Table 2 Products and main by-products in the oxidation process of cinnamaldehyde

[0089]

[0090] 2.3 Taking BiVO4-Ar-2h as an example, the effect of reaction conditions on the photocatalytic oxidation of cinnamaldehyde

[0091] This section mainly considers the effects of catalyst dosage, reaction time, and different reaction solvents on the preparation of benzaldehyde by oxygen oxidation of cinnamaldehyde catalyzed by BiVO4-Ar-2h, and the operation is carried out according to the conditions and steps in 2.1.

[0092] 2.3.1 Catalyst dosage

[0093] In the process of photocatalytic oxygen oxidation of cinnamaldehyde to prepare benzaldehyde, the amount of catalyst used has a significant effect on the reaction. In this experiment, the amount of catalyst used in the reaction was 10 mg, 30 mg, 50 mg and 70 mg respectively to explore the optimal reaction amount. The activity results obtained when the reaction was carried out for 10 hours are shown in Table 3.

[0094] It can be seen from the experimental results that the addition of the catalyst promotes the reaction. When 10 mg of catalyst was added, the cinnamaldehyde conversion rate and benzaldehyde yield were 2.3 times and 3 times that when no catalyst was added, respectively. Although the cinnamaldehyde conversion rate and benzaldehyde selectivity were improved compared to when no catalyst was added, the reaction rate and efficiency were still limited due to limited active sites. When the catalyst dosage increased to 30 mg, the cinnamaldehyde conversion rate and benzaldehyde selectivity increased by 4% and 3%, respectively. However, when the catalyst dosage was further increased to 50 mg, the conversion rate had no obvious increase, and the selectivity increased by only 3.5%. Continuing to increase the catalyst amount to 70 mg, the oxidation efficiency of the system did not improve, but decreased. It is possible that the catalyst concentration is too high, although it provides more active sites and reduces the utilization rate of light. Therefore, the optimal reaction dosage of the catalyst was determined to be 30 mg.

[0095] Table 3 Effect of catalyst dosage on cinnamaldehyde oxidation reaction

[0096]

[0097] 2.3.2 Response time

[0098] In the process of preparing benzaldehyde by photocatalytic oxygen oxidation of cinnamaldehyde in BiVO4-Ar-2h, the reaction time directly affects the reaction efficiency and product quality. In this experiment, the conversion of cinnamaldehyde in different reaction time periods was investigated, and the results are shown in Table 4. The reaction lasted for a total of 14 hours, and the conversion was detected every 2 hours.

[0099] The results show that in the early stage of the reaction, as the illumination time increases, the photocatalyst gradually activates and produces more active sites, thereby accelerating the oxidation reaction of cinnamaldehyde. At this time, the conversion rate of cinnamaldehyde gradually increases, and at the same time, the selectivity of benzaldehyde as the main product is also increasing. This is because at this stage, the reaction mainly proceeds along the path of generating benzaldehyde, and there are relatively few side reactions. As the reaction proceeds, the conversion rate of cinnamaldehyde and the selectivity of benzaldehyde are gradually increasing. When the reaction is carried out for 10 hours, the selectivity of benzaldehyde reaches the maximum value. After 10 hours, the conversion rate of cinnamaldehyde still keeps increasing, but the growth rate begins to slow down, because as the reactants are consumed, the reaction rate will naturally decrease gradually. As the reaction continues, the concentration of cinnamaldehyde gradually decreases, which may lead to a slowdown in the reaction rate and make the side reactions more significant in the competition. This creates conditions for benzaldehyde to be over-oxidized to benzoic acid, causing the selectivity of benzaldehyde to begin to decrease, resulting in a decrease in the yield of benzaldehyde. In a short time, the reaction is not complete and the conversion rate of cinnamaldehyde is low; while in a long time, although the oxidation of cinnamaldehyde is also ongoing, it will trigger a series of side reactions, reduce the selectivity of the product benzaldehyde, and increase energy consumption and cost. Therefore, determining the appropriate reaction time is the key to optimizing the photocatalytic oxidation process, and the optimal reaction time is determined to be 10h.

[0100] Table 4 Effect of reaction time on cinnamaldehyde oxidation reaction

[0101]

[0102] 2.3.3 Different solvents

[0103] This invention explores the effects of ethanol, acetonitrile, 1,2-dimethoxyethane, ethyl acetate, and N,N-dimethylformamide as solvents on the activity of BiVO4-Ar-2h photocatalytic oxidation of cinnamaldehyde. The results are shown in Table 5.

[0104] From the test results, it was found that the conversion effect of cinnamaldehyde was best when the solvent was acetonitrile, and the highest cinnamaldehyde conversion rate (68.1%) and the highest benzaldehyde selectivity (58.4%) could be achieved. This is because acetonitrile is a polar solvent that can dissolve a variety of organic substances, including reactants and products such as cinnamaldehyde and benzaldehyde. This wide solubility ensures that the reactants and products are fully dispersed and contacted in the solvent, which is conducive to the reaction. In addition, acetonitrile exhibits high chemical inertness under reaction conditions and is not easy to react with reactants or products. This characteristic ensures high selectivity and high conversion efficiency of the reaction and avoids the generation of unnecessary by-products. When ethanol was used as a solvent, it was found that ethanol was chemically active and easily reacted with cinnamaldehyde to form acetal, and the content was unstable, while the benzaldehyde yield was extremely low. Although 1,2-dimethoxyethane and ethyl acetate can also make the reaction go smoothly, the conversion effect of cinnamaldehyde in these two solvents is far inferior to that in acetonitrile. This may be because the polarity of 1,2-dimethoxyethane and ethyl acetate does not completely match the polarity of cinnamaldehyde and the photocatalyst. Using N,N-dimethylformamide as a solvent, only 6.6% benzaldehyde yield can be obtained. Although N,N-dimethylformamide is a highly polar solvent with good solubility for many organics, it may not provide the best microenvironment for cinnamaldehyde and photocatalysts in specific photocatalytic oxidation reactions. The polarity difference between the solvent and the reactants and catalysts may affect the intermolecular interactions and reaction efficiency. Therefore, after comprehensive consideration, acetonitrile is the best solvent for the preparation of benzaldehyde by photocatalytic oxygen oxidation of cinnamaldehyde by BiVO4-Ar-2h.

[0105] Table 5 Effect of solvent on oxidation reaction of cinnamaldehyde

[0106]

[0107] 2.3.4 Other reaction conditions

[0108] This section discusses the effects of external factors such as light, oxygen and catalyst on the reaction during the photocatalytic oxygen oxidation of cinnamaldehyde by BiVO4-Ar-2h.

[0109] The results are shown in Table 6. In the absence of light, the conversion rate of cinnamaldehyde decreased significantly by 27%, and the yield of benzaldehyde also decreased significantly by 40%. This result shows that light plays a vital role in the reaction system and can effectively promote the reaction rate. Further, when oxygen is excluded from the reaction system, the reaction process is significantly inhibited, and the yield of benzaldehyde drops sharply to only 2.6%, which can be regarded as no benzaldehyde generation. This fully demonstrates that oxygen is an indispensable key factor for the smooth oxidation reaction of cinnamaldehyde, and its presence has a decisive influence on the reaction efficiency. In addition, if no catalyst is added during the reaction, the conversion rate of cinnamaldehyde and the yield of benzaldehyde have a significant decrease of 58% and 69%, respectively. This data clearly shows the significant catalytic effect of the catalyst in this reaction system. It not only promotes the efficient progress of the reaction, but also significantly improves the efficiency of the target product generation, which is an important helper to ensure the smooth progress of the reaction. Therefore, light, oxygen and catalyst are the three key factors in the conversion of cinnamaldehyde to benzaldehyde. They work together in the reaction system to ensure the efficient and smooth progress of the reaction.

[0110] Table 6 Effect of other conditions on the oxidation reaction of cinnamaldehyde

[0111]

[0112] 2.5 Study on the active intermediates of preparing benzaldehyde by photocatalytic oxidation of cinnamaldehyde

[0113] 2.5.1 Active species quenching experimental method

[0114] (Step 1): Place 30 mg of BiVO4-Ar-2h at the bottom of the photoreactor, and purge with oxygen for 10 minutes to expel the air in the reactor. Connect the oxygen ball to the air outlet of the photoreactor and fill it with oxygen. (Step 2): Accurately weigh 5 mmol of cinnamaldehyde and 10 mL of acetonitrile in a 50 mL beaker, inject them into the photocatalytic reactor with a syringe, and then add a certain amount of active species quencher respectively. After mixing evenly, inject the solution into the photoreactor with a syringe. (Step 3): Stir in a dark environment for 30 minutes, turn on the light source after reaching the adsorption and desorption equilibrium, and start the active species quenching experiment of BiiVO4-Ar-2h photocatalytic oxidation of cinnamaldehyde. (Step 4): Take a sample every 2 hours to observe the changes in the product, and the reaction is carried out for 10 hours.

[0115] The quencher 2,2,6,6-tetramethylpiperidinyloxy (TEMPO) is used to quench free radicals, 0.5 mmol. The quencher p-benzoquinone (BQ) is used to quench superoxide anion free radicals, 0.5 mmol. The quencher furfuryl alcohol (FFA) is used to quench singlet oxygen, 0.5 mmol. The quencher tert-butyl alcohol (TBA) is used to quench hydroxyl free radicals, 5.0 mmol.

[0116] 2.5.2 Analysis of the results of the active species quenching experiment

[0117] Active species (such as superoxide radicals, hydroxyl radicals, singlet oxygen, etc.) usually play a key role in photocatalytic reactions. By quenching these active oxygen species, we can understand their specific role in the reaction, thereby revealing the detailed reaction mechanism of photocatalytic oxygen oxidation of cinnamaldehyde to prepare benzaldehyde. This part of the study used quenchers such as p-benzoquinone (BQ), tert-butyl alcohol (TBA), furfuryl alcohol (FFA), and triethanolamine (TEOA) to quench the superoxide radicals, hydroxyl radicals, singlet oxygen, and photogenerated holes generated during the oxidation of cinnamaldehyde.

[0118] According to the results of the active species quenching experiment, after adding different quenchers, the conversion efficiency of BiVO4-Ar-2h photocatalytic oxidation of cinnamaldehyde was reduced, indicating that the reaction was inhibited to varying degrees. Fig.10 As shown in the figure, after adding p-benzoquinone, triethanolamine, tert-butanol and furfuryl alcohol respectively, the conversion rate of cinnamaldehyde by BiVO4-Ar-2h photocatalytic oxidation decreased by 15%, 40%, 48% and 34%, respectively, and the benzaldehyde yield decreased by 15%, 39%, 29% and 21%, respectively. It shows that superoxide radicals, photogenerated holes, hydroxyl radicals and singlet oxygen play a very important role in the process of BiVO4-Ar-2h photocatalytic oxidation of cinnamaldehyde. Among them, hydroxyl radicals play the most decisive role in the conversion efficiency of cinnamaldehyde. However, after adding tert-butanol, the selectivity of benzaldehyde only decreased by 6%. It shows that hydroxyl radicals can significantly promote the oxidation of cinnamaldehyde, but they are not the decisive factor affecting the selectivity of benzaldehyde. Secondly, photogenerated holes also play a very obvious role in the conversion efficiency of cinnamaldehyde, especially the most obvious effect on the selectivity of benzaldehyde. After adding triethanolamine, the conversion rate of cinnamaldehyde decreased by 40%, and the selectivity of benzaldehyde was directly reduced to the original 6%. This indicates that cinnamaldehyde can selectively generate benzaldehyde during the transformation process, and photogenerated holes play a decisive role.

[0119] 2.6 Exploration of the reaction sites of cinnamaldehyde

[0120] According to the activity test results, cinnamaldehyde mainly produces benzaldehyde during the oxidation process. In order to explore whether the >C=C< double bond of cinnamaldehyde is directly oxidized and cleaved during the oxidation process of cinnamaldehyde, or whether the C=O double bond of the aldehyde group preferentially participates in the reaction, cinnamic acid, styrene and benzaldehyde were selected as reaction substrates, and the conversion was analyzed under the photocatalytic oxidation conditions of Section 2.1 after 10 hours of reaction. The photocatalytic oxidation of cinnamaldehyde (a), cinnamic acid (b), styrene (c) and benzaldehyde (d) as substrates is as follows:

[0121]

[0122]

[0123] According to the experimental results scheme 3-1b, it can be seen that after the reaction of cinnamic acid, almost no benzaldehyde is obtained, and no other reaction products are generated. From a structural analysis, cinnamic acid contains a carboxyl group (-COOH) and a >C=C< double bond connected to the benzene ring. The carboxyl group is a strong electron-withdrawing group, which attracts electrons from the >C=C< double bond through the conjugation effect, resulting in a decrease in the electron cloud density of the >C=C< double bond. This decrease in electron cloud density makes the >C=C< double bond relatively stable and less easily oxidized. Cinnamaldehyde contains an aldehyde group (-CHO) and a >C=C< double bond connected to the benzene ring. The carbonyl group (C=O) in the aldehyde group is also an electron-withdrawing group, but its conjugation effect on the >C=C< double bond is usually not as strong as that of the carboxyl group. However, the oxygen atom on the aldehyde group can form p-π conjugation with the π electrons on the >C=C< double bond, which may increase the electron cloud density of the >C=C< double bond to a certain extent, making it relatively easier to be oxidized. This result also fully demonstrates that the synthesis of benzaldehyde does not include the path of cinnamaldehyde being oxidized to cinnamic acid and then further cleaving the side chain >C=C< double bond of cinnamic acid.

[0124] Styrene was subjected to photocatalytic oxidation under the same conditions, and the results are shown in Scheme 3-1c. After 10 hours of oxidation reaction, styrene hardly participated in the conversion, and almost no benzaldehyde was generated. Therefore, although the electron cloud density of the >C=C< double bond outside the benzene ring of styrene is relatively high, this does not mean that it is easily oxidized. Therefore, under the catalysis of bismuth vanadate, oxygen cannot oxidize styrene well, and the presence of aldehyde groups in cinnamaldehyde promotes its conversion to benzaldehyde.

[0125] In order to solve the problem that the selectivity of benzaldehyde gradually decreases after cinnamaldehyde is converted into benzaldehyde, benzaldehyde was subjected to photocatalytic oxidation reaction under the same conditions. The results showed that after only 2 hours of reaction, about 80% of benzaldehyde was converted, almost all of which was converted into benzoic acid. As time went on, the remaining benzaldehyde was almost no longer converted. Therefore, after cinnamaldehyde was converted into benzaldehyde, it was easy to be further oxidized into benzoic acid as the concentration of benzaldehyde increased. When the concentration of benzaldehyde reached a high level, the oxidation rate of benzaldehyde was much faster than the rate of benzaldehyde generation. Therefore, under this catalytic oxidation condition, cinnamaldehyde can be effectively converted into benzaldehyde, but inhibiting the further oxidation of benzaldehyde into benzoic acid will be a crucial research content.

[0126] 2.7 Speculation of the oxidation pathway of cinnamaldehyde

[0127] Based on the active species quenching experiment, it can be inferred that the reaction mechanism of BiVO4-Ar-2h photocatalytic oxygen oxidation of cinnamaldehyde to prepare benzaldehyde may be mainly mediated by photogenerated carriers. Combining the above calculation results with the analysis and detection results of each component in the oxidation process of cinnamaldehyde by GC-MS and GC, the following analysis is made: Fig.11 According to the adsorption energies of cinnamaldehyde molecules and oxygen molecules on the BiVO4-Ar-2h adsorption surface, the optimal adsorption energy of oxygen molecules (18.053 eV) is much greater than the optimal adsorption energy of cinnamaldehyde (0.704 eV). Therefore, it is believed that the adsorption of O2 molecules is the first step in the reaction.

[0128] First, photoexcitation BiVO4-Ar-2h generates photogenerated electron-hole pairs. The photogenerated electrons first act on the molecular oxygen adsorbed on the surface of BiVO4-Ar-2h, and the O–O bond is activated, preparing for the next oxidation reaction. The photogenerated holes act on the >C=C< double bond of cinnamaldehyde to generate a cinnamaldehyde radical cation intermediate. The activated oxygen acts on the >C=C< double bond of the cinnamaldehyde radical cation, and the >C=C< double bond reacts with the activated molecular oxygen through [2+2] cycloaddition to generate a dioxocyclic intermediate II. The dioxocyclic intermediate is extremely unstable and quickly decomposes into benzaldehyde III or oxygen-containing three-membered ring compound VI. Due to the large amount of molecular oxygen, benzaldehyde will be further over-oxidized to benzoic acid IV. Since the oxygen-containing three-membered ring compound is also very unstable, it is easy to decompose for the next reaction. There are three possible cleavage modes for oxygen-containing three-membered ring compounds, namely, isomerization to 2-hydroxyacetophenone VII or styrene oxide VIII, and cleavage of the three-membered ring to generate benzaldehyde III, which provides a new pathway for the generation of benzaldehyde and may be a favorable factor for improving the selectivity of benzaldehyde. Styrene oxide can also be isomerized in one step to acetophenone and phenylacetaldehyde, which are more stable in structure.

[0129] 2.8 Mechanism analysis of the oxidation of cinnamaldehyde to prepare benzaldehyde

[0130] Combined with the results of the active quenching experiment, based on the previous characterization and test results, a possible mechanism for the preparation of benzaldehyde by oxygen oxidation of cinnamaldehyde catalyzed by BiVO4-Ar-2h was proposed, and the following diagram was drawn: Fig.12 Schematic diagram shown.

[0131] First, under light excitation, BiVO4-Ar-2h produces photogenerated – and h + , the electrons in the VB of BiVO4-Ar-2h jump to the CB, and the photoinduced holes remain in the VB. After being excited by light, BiVO4-Ar-2h can effectively adsorb O2, and the photogenerated carriers that migrate to the surface can transfer electrons with the adsorbed O2. The CB edge potential of BiVO4 (-0.38eV) is lower than that of O2 / ·O2 –(–0.33eV) is more negative, so O2 can react with electrons to form ·O2 – In addition, OVs have a strong ability to capture electrons. Some electrons from the conduction band of BiVO4-Ar-2h can be captured by OVs. These captured electrons can react with O2 adsorbed on BiVO4-Ar-2h to generate O2 – , and O2 is easily oxidized to singlet state by photogenerated holes on the catalyst surface. 1 O2. These reactive oxygen species are key to achieving efficient oxidation of cinnamaldehyde.

[0132] At the same time as molecular oxygen is adsorbed and activated, the h + It can combine with a π electron on the double bond of cinnamaldehyde>C=C<, turning one of the double bond carbons into a carbon cation. The other double bond carbon retains a π electron and forms a carbon radical I. After that, ·O2 – It acts on carbon free radical I to obtain intermediate II. The terminal oxygen atom attacks the carbon cation to form a four-membered ring intermediate III, which is desorbed from the catalyst surface. Finally, the four-membered ring of intermediate III is cleaved to generate benzaldehyde IV. The quenching experiment results show that there is a large amount of h + and 1 O2 is considered to be the main species involved in the main reaction. 1 O2 can be obtained by – H + After cinnamaldehyde is adsorbed, the side chain electronic structure is rearranged, and a carbon cation is formed at the α-carbon of the phenyl group, becoming 1 O2 attacks the site to generate intermediate VI. After electron rearrangement, a four-membered ring intermediate III is also obtained and desorbed from the catalyst surface. Finally, the four-membered ring of intermediate III is cleaved to generate benzaldehyde. The accumulated ·OH in the system can also further oxidize benzaldehyde to benzoic acid V.

[0133] Example 3

[0134] 3.1 Catalyst xBi 0 Preparation method of BiVO4

[0135] (Step 1) Weigh bismuth nitrate pentahydrate and ammonium metavanadate according to the masses shown in Table 7, and then perform the reaction in Experiments 1 to 5 according to the conditions and steps of subsequent Steps 2 to 7;

[0136] Table 7 Mass and molar ratio of reactants in experiments 1 to 5

[0137]

[0138] (Step 2) Dissolve the bismuth nitrate pentahydrate weighed in Step 1 in a 100mL beaker containing 30mL ethylene glycol, and record the solution as A. (Step 3) Dissolve the ammonium metavanadate weighed in Step 1 in a 100mL beaker containing 30mL deionized water, and record the solution as B. (Step 4) Slowly drip solution B into solution A while stirring with a magnetic force, and then stir and mix thoroughly for 30min, the speed of the magnetic stirrer is 500rpm / min, and then add ammonia water with a mass fraction of 25.0-28.0% dropwise to adjust the solution pH to 7, and continue stirring for 1h. (Step 5) Pour the suspension into the polytetrafluoroethylene liner of a 100mL high-pressure reactor, heat it to 160℃ in an oven, and keep it warm for 8h. (Step 6) The obtained sample is washed three times with 40mL of anhydrous ethanol and deionized water respectively, and then placed in a vacuum drying oven and kept warm at 60℃ for 10h. (Step 7) The dried sample was placed in a tube furnace, the temperature was raised to 450°C at a heating rate of 5°C / min, and kept at this temperature for 2h to obtain the product.

[0139] 3.2 Results and discussion of catalyst characterization

[0140] 3.2.1BiVO4-Ar-2h and xBi 0 XRD data analysis of / BiVO4

[0141] exist Fig.13 In a, the observed diffraction peaks with 2θ values ​​of 18.6°, 28.6°, 28.8°, 30.5° and 34.5° are consistent with the characteristic diffraction peaks of (101), (103), (013), (004) and (200) crystal planes recorded in the standard card of monoclinic BiVO4 (JCPDS No.83-1699), respectively. 0 / BiVO4 sample, additional diffraction peaks appeared in its XRD spectrum, located at 2θ = 27.2, 38.1 and 39.7°, which can be attributed to the (012), (104) and (110) crystal planes of elemental bismuth, which is consistent with the standard card data of monoclinic elemental bismuth (JCPDS No.85-1330). It is worth noting that although at 0.2Bi 0 / BiVO4 and 0.4Bi 0 No obvious characteristic peak of elemental bismuth was detected in the / BiVO4 sample, but Fig.13 b shows that the diffraction peaks of these two samples are shifted to a higher angle by about 0.2° compared with the characteristic diffraction peaks of BiVO4, and are similar to those of 0.6Bi 0This phenomenon indicates that although the characteristic peaks of Bi atoms are not directly shown in the XRD data, the in-situ generated Bi atoms have entered the lattice gap of BiVO4, resulting in a decrease in the lattice spacing. 0 / BiVO4, 0.4Bi 0 / BiVO4 and 0.6Bi 0 The main characteristic signals of XRD of 0.8Bi / BiVO4 are consistent with those of BiVO4-Ar-2h, indicating that the in-situ generated Bi atoms do not cause significant changes in the BiVO4 structure. 0 In the XRD data of / BiVO4, only the signal of monoclinic bismuth was observed, which indicates that when the amount of bismuth nitrate pentahydrate added is insufficient, Bi 3+ The bismuth ions are reduced to bismuth atoms in large quantities instead of generating BiVO4. This result indirectly confirms that there is a competitive relationship between the reduction reaction of bismuth ions and the generation reaction of BiVO4.

[0142] 3.2.2BiVO4-Ar-2h and xBi 0 Analysis of Fourier transform infrared spectroscopy (FTIR) data of / BiVO4

[0143] Fig.14 It not only reveals more structural details, but also indicates the changes in the catalyst structure after Bi atoms are loaded. Fig.14 Except for 0.8Bi 0 / BiVO4 data, other xBi 0 The infrared images of the BiVO4 catalysts are all between 400-1000 cm -1 The typical BiVO4 structure of Bi-O (470 cm -1 ) and VO bonds. In particular, VO4 3- Tetrahedral bending and stretching vibrations are between 550 and 950 cm -1 The broad peak produced is its characteristic signal. 0 / BiVO4 Fig.13 There is no BiVO4 signal in the XRD data of a, and all that appears are monoclinic bismuth crystal signals. Fig.14 Medium 1020, 845 and 740cm -1 The three signals are the characteristic absorption of monoclinic bismuth crystal. 0 / BiVO4 starts at 1020cm -1 The signal begins to appear, indicating that bismuth atoms have been loaded in BiVO4, although the signal of monoclinic bismuth has not yet appeared in its XRD. 0In the infrared spectrum of BiVO4, as the content of bismuth atoms increases, 845 and 740 cm -1 Two characteristic signals become stronger, from VO4 3- The characteristic broad peak is revealed.

[0144] 3.2.3BiVO4-Ar-2h and xBi 0 XPS data analysis of BiVO4

[0145] Fig.15 Important information about the chemical state and electronic structure of the three elements bismuth, vanadium and oxygen in the catalyst can be obtained.

[0146] Fig.15 a and Fig.15 b is BiVO4-Ar-2h and xBi 0 The 4f characteristic signals of Bi element in BiVO4, of which the signals with binding energies of 159.0 and 164.4 eV are respectively attributed to the 4f of Bi ion. 7 / 2 and 4f 5 / 2 In front of these two signals, the 4f peaks belonging to metal bismuth can be fitted. 7 / 2 and 4f 5 / 2 Characteristic peaks, 157.7 and 163.1 eV. This shows that in this preparation method, even when the molar ratio of ammonium metavanadate to bismuth nitrate pentahydrate is 1:1, there is still a small amount of Bi 3+ The ions are reduced to bismuth atoms. However, due to its low content, its corresponding signal cannot be observed in XDR and FT-IR. 0 / 4f of Bismuth in BiVO4 7 / 2 and 4f 5 / 2 The characteristic peak intensity increases significantly with the increase of ammonium vanadate content during the preparation process. 0 / BiVO4's Bi 3+ The characteristic peaks of ions shifted to a higher binding energy by about 0.1 eV.

[0147] exist Fig.15 In the XPS spectrum of V 2p of c, the peaks at binding energies of 516.6 and 524.1 eV are attributed to V 2p 3 / 2 and V 2p 1 / 2 ; At the same time, in xBi 0 The binding energy of the two signals in / BiVO4 also appears similar to that of xBi 0 The characteristic peak of Bi ions in MgSO4 / BiVO4 changes similarly, with an increase of 0.4 eV.

[0148] Fig.15In the O1s spectrum of BiVO4-Ar-2h shown in d, the component peaks at 529.7, 531.1 and 533 eV are respectively attributed to lattice oxygen (O latt ), oxygen vacancies (O V ) and oxygen adsorbed on the sample surface (O ads ). Compared with BiVO4-Ar-2h, xBi 0 The most obvious change in the O1s spectrum of BiVO4 is the addition of O latt The binding energies of O V The rapid decrease in signal strength indicates that xBi 0 / BiVO4 has a decreasing number of oxygen vacancies. This is consistent with the 0 The increase in the binding energy of the characteristic signals of bismuth and vanadium ions in / BiVO4 corresponds to that of xBi 0 Compared with BiVO4 / BiVO4, the two metal ions in BiVO4-Ar-2h have lost electrons, which increases the binding energy of the inner electrons of the metal ions. This confirms that the in-situ reduction of bismuth ions is carried out at the site of oxygen vacancies. When there are oxygen vacancies, bismuth ions and vanadium ions are not normal +3 and +5 valences; this makes such bismuth ions obtain a higher valence than Bi +3 Fewer electrons make it easier to be reduced. When such bismuth ions are reduced, the vanadium ions at that site will become +5 valence. When the number of +2 valence ions in the bismuth ion decreases, Bi 3+ The relative content will increase; while the non-+5 valence vanadium ions will all become +5 valence when the bismuth ions are in situ reduced. Therefore, if we consider the two metal ions in the catalyst, both are cases of reducing electrons, corresponding to the increase of characteristic signals.

[0149] 3.2.4 0.6Bi 0 Crystal structure and energy dispersive spectrometer (EDS) analysis of BiVO4

[0150] 0.6Bi 0 TEM image of BiVO4 Fig.16 a and Fig.16 In b), the lattice spacings of 0.3926 and 0.3765 nm in the surface particles correspond to the (003) and (101) crystal planes of the monoclinic bismuth crystal, respectively, confirming that it is the bismuth obtained by in-situ reduction. On the surface where the particles are attached, the lattice spacings of 0.2880 nm and 0.3078 nm correspond to the (004) and (112) crystal planes of the monoclinic BiVO4 crystal, respectively.

[0151] At the same time, 0.6Bi 0 / EDS image of BiVO4( Fig.16 c) The Bi, V, and O elements are evenly distributed, indicating that the catalyst has good uniformity.

[0152] 3.2.5BiVO4-Ar-2h and xBi 0 Morphology and size analysis of / BiVO4

[0153] By comparing BiVO4-Ar-2h and xBi 0 / SEM image of BiVO4( Fig.17 ), it can be seen that with the appearance of in-situ reduced Bi, its effect on the microstructure of the catalyst is very obvious. BiVO4-Ar-2h is a relatively regular olive-shaped particle with a smooth surface and a few irregular lines ( Fig.17 (a1–a3)). As the amount of Bi increases, 0.2Bi 0 / BiVO4 morphology changes to a four-pointed star shape ( Fig.17 (b1–b3)), the other three xBi 0 / BiVO4 catalyst is spherical ( Fig.17 (c–e)); at the same time, 0.4Bi 0 / BiVO4, 0.6Bi 0 / BiVO4 and 0.8Bi 0 / BiVO4 all showed obvious particles, which should be the Bi element generated by in-situ reduction. When the molar ratio of ammonium metavanadate and bismuth nitrate pentahydrate was 1.6:1, the 0.6Bi 0 / BiVO4 has a clear layered structure. This is also a characteristic of the monoclinic scheelite BiVO4 crystal structure, that is, the crystal is perpendicular to the Bi 3+ and V 5+ The c-axis direction of the up-and-down displacement is very easy to crack, producing a flat cleavage surface ( Fig.17 (d1–d3)). Since cinnamaldehyde is a planar molecule, the appearance of a large number of cleavage planes will not only increase the specific surface area of ​​the catalyst, but also facilitate the entry of cinnamaldehyde molecules into the interlayers, making full use of the active sites on each cleavage plane to react. 0 / BiVO4 crystal surface is heavily attached, and even the gaps around the layered structure are completely filled with particles. This will inevitably affect the activity of the catalyst, resulting in a possible decrease in the conversion rate of cinnamaldehyde and the selectivity of benzaldehyde.

[0154] 3.2.6 BiVO4-Ar-2h and xBi 0 Analysis of specific surface area, pore size and pore volume distribution of / BiVO4

[0155] According to the appearance observed by SEM, the effect of loaded bismuth on the specific surface area, pore size and pore volume distribution of the catalyst was studied by Brunauer-Emmett-Teller (BET) and Barrett-Joyner-Halenda (BJH) methods. The results are shown in Fig.18 and Table 8.

[0156] Fig.18 The N2- adsorption-desorption isotherms of BiVO4-Ar-2h and xBi 0 The isotherms of / BiVO4 all conform to the typical IV type isotherm characteristics, and the inflection point at P / P0=0.1 is not obvious, which indicates a large amount of overlap of monolayer coverage and the beginning of multilayer adsorption. And with the increase of Bi loading, this overlap phenomenon is more significant, and multilayer adsorption begins at an earlier stage. With the increase of relative pressure, the adsorption amount gradually increases exponentially, indicating that the catalyst is in a state of multilayer adsorption. Moreover, 0.6Bi 0 / BiVO4 has the largest adsorption capacity, and when the Bi loading continues to increase, 0.8Bi 0 The decrease in the adsorption of / BiVO4 also confirms that the excessive Bi loading leads to partial blockage of the catalyst pores and affects the adsorption of the catalyst. The appearance of an H3-type hysteresis loop in the high-pressure region of the isotherm (P / P0=0.8–1.0) confirms that capillary condensation occurs in the catalyst pores, which is direct evidence of the existence of a mesoporous structure.

[0157] Pore ​​size distribution curve ( Fig.18 b) shows that the pore sizes of these catalysts are mainly concentrated between 2 and 50 nm, further confirming the characteristics of their mesoporous structure.

[0158] The specific surface area, pore size and pore volume data of the catalyst in Table 8 clearly reflect the effect of in-situ reduced Bi loaded on the surface of BiVO4 crystals. Appropriate loading of Bi will increase the specific surface area, pore size and pore volume of BiVO4, but if the loading is too much, these values ​​will decrease. 0 / BiVO4 has the most obvious increase in specific surface area and pore volume, which are about 10 times that of BiVO4-Ar-2h. 0 / BiVO4 has an inflection point due to 0.6Bi 0 The pore size of 0.8BiVO4 is consistent with that of BiVO4-Ar-2h. For the planar substrate cinnamaldehyde, a slight decrease in pore size does not have as significant an effect on catalytic activity as a significant increase in specific surface area and pore volume. 0 The specific surface area and pore volume of BiVO4 are higher than those of 0.6Bi 0 / BiVO4 decreased by 41% and 30% respectively, indicating that excessive loading of Bi will indeed reduce the activity of the catalyst.

[0159] Table 8 BiVO4-Ar-2h and xBi 0 / Structural characteristics of BiVO4

[0160]

[0161] 3.2.7 BiVO4-Ar-2h and xBi 0 Analysis of absorption edge, bandgap and light absorption performance of BiVO4

[0162] The BiVO4-Ar-2h and xBi 0 / BiVO4 sample light absorption capacity, the results are as follows Fig.19 As shown in a. Fig.19 a It can be seen that BiVO4-Ar-2h and xBi 0 / BiVO4 has strong absorption in the visible light region, and after loading Bi, xBi 0 / BiVO4's visible light absorption edge shifts toward the long-wave direction, which means that xBi 0 / BiVO4 electronic structure changes, narrowing the band gap between the valence band and the conduction band. With the increase of Bi loading, 0.6Bi 0 The visible light absorption edge of BiVO4 reaches a maximum value of 546nm; further increase of Bi slightly reduces the absorption edge.

[0163] BiVO4-Ar-2h and xBi 0 The bandgap of BiVO4 is determined by the Tauc equation (αhυ) 1 / n =A(hυ–E g ) is calculated. According to (αhυ) 1 / n The band gap spectrum is calculated by the relationship between hυ and Fig.19 b. By Fig.19 b It can be seen that BiVO4-Ar-2h, 0.2Bi 0 / BiVO4, 0.4Bi 0 / BiVO4, 0.6Bi 0 / BiVO4 and 0.8Bi 0 / The band gap energy of BiVO4 (E g ) are 2.38, 2.36, 2.34, 2.29 and 2.35 eV, respectively, which proves that Bi loading can narrow the band gap. 0 After / BiVO4 reaches the minimum value, increasing the Bi loading will slightly widen the band gap. 0Among the five photocatalysts, the electrons in BiVO4 require the least energy to jump from the valence band to the conduction band, and have better photocatalytic activity.

[0164] The valence band potential (E) of each catalyst was obtained by XPS valence band spectrum. VB,XPS ), BiVO4-Ar-2h, 0.2Bi 0 / BiVO4, 0.4Bi 0 / BiVO4, 0.6Bi 0 / BiVO4 and 0.8Bi 0 / The corresponding valence band potential E of BiVO4 VB,XPS They are 1.37, 1.41, 1.59, 2.00 and 2.11 eV respectively ( Fig.19 c).

[0165] E of the corresponding standard hydrogen electrode VB (E VB,NHE ) can be based on (in is the work function of the instrument 4.2eV) and calculated that BiVO4-Ar-2h, 0.2Bi 0 / BiVO4, 0.4Bi 0 / BiVO4, 0.6Bi 0 / BiVO4 and 0.8Bi 0 E of BiVO4 VB,NHE They are 1.13, 1.17, 1.35, 1.74 and 1.87 eV respectively. According to the empirical formula E CB =E VB -E g (Among them, E CB is the conduction band energy, E g is the band gap energy, E VB is the valence band energy), we can calculate that the conduction band energies of the catalysts are –1.25, –1.19, –0.99, –0.55 and –0.48 eV respectively, and the corresponding energy band positions are as follows: Fig.19 d. Fig.19 d It can be seen that the CB values ​​of all catalysts are smaller than that of O2 reduced to ·O2 - The electrode potential (E 0 =-0.33V vs.NHE, pH=0), indicating that BiVO4-Ar-2h and xBi 0 / BiVO4 can reduce O2 to ·O2 - , while O2 - It is considered to be one of the main oxygen species for the oxidation of olefins by oxygen. When metal Bi is loaded onto BiVO4, the CB values ​​are closer to It can ensure the smooth progress of the oxidation reaction while avoiding the decrease in benzaldehyde selectivity caused by excessive oxidation. 0 / BiVO4 has a narrower band gap, making its electrons more easily excited by light energy to generate photogenerated electrons.

[0166] 3.2.8 Photoelectrochemical testing

[0167] 3.2.8.1 Test methods

[0168] Photoelectrochemical tests were performed on a CHI 760E electrochemical workstation using a standard three-electrode system. The counter electrode and reference electrode were platinum electrode and Ag / AgCl electrode, respectively, and the photocatalyst electrode was the working electrode. The working electrode preparation method was as follows: 10 mg of catalyst and 20 μL of nafion solution were added to 200 μL of anhydrous ethanol, and after ultrasonication for 90 min, the suspension was evenly coated on an area of ​​1 cm 2 The surface of indium tin oxide (FTO) conductive glass with a diameter of (1cm×1cm) was dried naturally to obtain a working electrode. In the photoelectrochemical test, 0.5M Na2SO4 was used as the buffer solution. A 300W xenon lamp with a 400nm cutoff filter was used as the light source for the transient photocurrent response test. The electrochemical impedance spectroscopy (EIS) of the catalyst electrode was tested in a dark environment under the conditions of an AC amplitude of 5mV and a frequency range of 0.01–1000kHz.

[0169] 3.2.8.2 Test results analysis

[0170] BiVO4-Ar-2h and xBi 0 / BiVO4 transient photocurrent density changes as Fig. 20 a. After loading Bi, xBi 0 / BiVO4 exhibits a higher photocurrent density than / BiVO4 under illumination. 0 / BiVO4 and 0.6Bi 0 The maximum photocurrent density of BiVO4 is about 0.06 μA·cm –2 , which is about 0.035μA·cm compared with BiVO4-Ar-2h –2 The photocurrent density increased by about 1.7 times. However, when the Bi load continued to increase, 0.8Bi 0 / BiVO4 decreases to the same level as 0.2Bi 0 / BiVO4 equivalent level.

[0171] Combination Fig. 20 b Electrochemical impedance spectroscopy (EIS Nyquist), found that after loading Bi, xBi 0 / BiVO4 arc radius is significantly reduced, especially 0.6Bi 0 / BiVO4 has the smallest arc radius. This indicates that xBi 0 / BiVO4 has lower charge transfer resistance than BiVO4-Ar-2h; at the same time, xBi 0 / BiVO4 interface charge transfer rate is accelerated. This not only confirms the results of the photocurrent density test, but also reveals from an electrochemical perspective the optimization of the internal charge transfer mechanism of the catalyst after Bi loading: it not only promotes 0 The separation of photogenerated carriers of BiVO4 / BiVO4 also accelerates the charge transfer process at the interface and improves the efficiency of the photocatalytic reaction.

[0172] Example 4

[0173] 4.1 Photocatalytic performance test

[0174] The test was performed according to the method in Section 2.1 of Example 2.

[0175] 4.2 Analysis of photocatalytic performance test results

[0176] 4.2.1 BiVO4-Ar-2h and xBi 0 / BiVO4 is used as a catalyst to catalyze the oxidation of cinnamaldehyde by oxygen. Fig.21 a) Benzaldehyde selectivity ( Fig.21 b) Benzaldehyde yield ( Fig.21 c) Analysis

[0177] After loading Bi, the reaction is xBi 0 The conversion rate of cinnamaldehyde under the catalysis of BiVO4 was 1.45 times higher than that under the catalysis of BiVO4-Ar-2h, even in the first 2 hours of analysis, and even 2.32 times. And at the subsequent sampling points, the conversion rate increased rapidly. After 10 hours of reaction, xBi 0 The conversion rate of cinnamaldehyde under the catalysis of xBiVO4 is above 75%, even exceeding 90%, while the conversion rate under the catalysis of BiVO4-Ar-2h is less than 60%. 0 / BiVO4, with Bi 0 As the loading amount increased, the conversion rate of cinnamaldehyde showed a trend of increasing first and then decreasing. 0 / BiVO4 reaches the best performance. This shows that the loaded elemental Bi is the key active site; but when there is too much Bi on the surface, the utilization rate of its active sites will be affected and the catalytic activity will decrease.

[0178] The effect of Bi loading on benzaldehyde selectivity is particularly significant. 0The benzaldehyde selectivity under 0.6Bi / BiVO4 catalysis is over 45%, which is more than twice that under BiVO4-Ar-2h catalysis. 0 When catalyzed by 0.6BiVO4, the selectivity of benzaldehyde reached 58.8% at the first sampling; at the second sampling (4 hours), it reached the maximum value of 61.9%. If the selectivity increase trend of the first two samplings extends to the reaction start time, its benzaldehyde selectivity exceeds 55%. Just as some catalysts reach the highest selectivity at the beginning of the reaction, 0.6BiVO4 0 / BiVO4 has a catalytic life of only 8 hours. 0 When catalyzed by / BiVO4, the selectivity of benzaldehyde was basically the same as that under BiVO4-Ar-2h after 8 hours of reaction, and was finally surpassed by it. Therefore, it is speculated that during the reaction, BiVO4 without Bi loading will gradually reduce Bi ions to Bi element during the catalytic process, so that its catalytic activity is gradually improved.

[0179] And xBi 0 / BiVO4 also faces the same situation, and too high Bi content will significantly reduce the catalyst specific surface area (0.8Bi 0 / BiVO4 vs. 0.6Bi 0 / BiVO4 decreased by more than 40%); Fig.17 It is also shown that too much Bi will cause the layered structure of the catalyst to disappear.

[0180] 4.2.2 0.6Bi 0 / BiVO4 as an example, SEM analysis of the catalyst before and after the reaction

[0181] The 0.6Bi after reaction 0 / SEM of BiVO4( Fig. 22 ) and 0.6Bi before reaction 0 / BiVO4( Fig.17 d) and 0.8Bi 0 / BiVO4( Fig.17 e) by comparing the above conclusion: the photogenerated electrons in the reaction will convert Bi 3+ Reduction increases the amount of Bi on the catalyst surface. However, too much Bi on the catalyst will have a certain inhibitory effect on the selectivity of the reaction.

[0182] 4.2.3 0.6Bi 0 / BiVO4 as an example, a cycle experiment was conducted

[0183] 4.2.3.1 Cycle experiment

[0184] After each 10-hour activity test, the reaction mixture was centrifuged to separate the reaction substrate and the catalyst, and then the catalyst was centrifuged three times in a row with 160 mL of ethanol divided into four equal parts, and then vacuum dried at 60 ° C for 10 hours and used for the next cycle test. A total of 5 cycle experiments were carried out.

[0185] 4.2.3.2 Result analysis

[0186] Cyclic stability test data ( Fig.23 ) and 0.6Bi after five cycles 0 / XRD of BiVO4( Fig.24 a) and FT-IR( Fig.24 b) The data show that although the reaction process will convert Bi into 3+ However, the crystal structure and chemical bond connection mode of the catalyst did not change significantly after repeated use; at the same time, the used catalyst could be effectively removed of adsorbed reactants and products by simple treatment. Fig.23 The data show that after 5 cycles, although the cinnamaldehyde conversion rate and benzaldehyde selectivity decreased to a certain extent, they still remained above 90% of the newly prepared ones, indicating that the catalyst has good stability and a long service life.

[0187] 4.3 Photocatalytic mechanism

[0188] 4.3.1 Experiment on the selective oxidation of cinnamaldehyde to benzaldehyde by oxygen in the dark room without catalyst and oxygen and with filter

[0189] In clarifying 0.6Bi 0 Before studying the mechanism of selective oxidation of cinnamaldehyde to benzaldehyde by oxygen with BiVO4 photocatalysis, it is necessary to clarify the roles of catalyst, oxygen and light in the reaction, especially the experiments on light source. In addition to the experiments in completely dark conditions using heat instead of light, since the light emitted by the xenon lamp still contains a certain amount of ultraviolet light, it is necessary to discuss the effect of ultraviolet light on the reaction in the illumination experiment. Considering the above factors, several experiments need to be carried out, namely, selective oxidation of cinnamaldehyde to benzaldehyde by oxygen without catalyst, without oxygen, in dark room conditions and with filters. The experimental results are shown in Table 9.

[0190] Table 9 Effects of catalyst, oxygen, light and UV light on the oxidation reaction of cinnamaldehyde

[0191]

[0192] 1. General reaction conditions: 5 mmol of cinnamaldehyde, 30 mg of photocatalyst, 10 mL of acetonitrile, oxygen balloon, 300 W xenon lamp, room temperature. 2. Reactions were run using a 400 nm UV cutoff filter.

[0193] First, cinnamaldehyde can be oxidized by oxygen to generate a series of oxidation products such as cinnamic acid, benzaldehyde and benzoic acid without any catalyst. However, the reaction is not only extremely inefficient, but also has low selectivity for benzaldehyde, with the benzaldehyde content in the product being less than 10%. Therefore, the use of catalysts in the reaction of preparing benzaldehyde by selective oxidation of cinnamaldehyde with oxygen mainly plays a role in improving reaction efficiency and benzaldehyde selectivity. As one of the reactants, the oxidant of the oxidation reaction of cinnamaldehyde, and the raw material for producing other highly oxidizing oxygen species, the role of oxygen reaction is obvious from the data in Table 9. Of course, during the reaction, although argon was used for purging, the oxygen adsorbed on the surface of the catalyst and the small amount of oxygen that may be introduced by adding acetonitrile and cinnamaldehyde will still cause oxidation of cinnamaldehyde, but only 2.3% of benzaldehyde is obtained, which is almost negligible. It is confirmed that in the absence of oxygen, the reaction is basically difficult to continue and benzaldehyde is generated. There are two aspects of the effect of light on the reaction: in addition to initiating the photoreaction, since the light emitted by the xenon lamp still contains a certain amount of ultraviolet rays, it is necessary to determine the effect of ultraviolet rays on the reaction through a filter experiment. Under darkroom conditions, heating to near the boiling point of the solvent was used instead of light source to provide energy. Under thermal reaction conditions, the cinnamaldehyde conversion rate dropped by more than 40% compared with the blank, but the benzaldehyde selectivity increased by more than 10 percentage points. This shows that the oxygen species produced in the photoreaction will indeed trigger some side reactions under the premise of bringing higher efficiency. Therefore, such oxygen species cannot be produced under thermal reaction conditions, which improves the benzaldehyde selectivity; but at the same time, the efficiency of the reaction also drops significantly due to the inability to produce oxygen species with efficient reactions. The filter experimental data further illustrates the influence of oxygen species on reaction efficiency and selectivity. Under the irradiation of a light source with completely removed ultraviolet rays, although the reaction efficiency (cinnamaldehyde conversion rate) dropped by 12.5%, the benzaldehyde selectivity increased by nearly 12% (11.8%) at the same time. Such data show that ultraviolet rays produce more oxygen species that bring side reactions, but the influence on oxygen species that bring efficient reactions is relatively limited.

[0194] 4.3.2 Active species quenching experiment

[0195] The method for the active species quenching experiment is the same as that in Section 2.5.1 of Example 2. The experimental results are analyzed as follows:

[0196] In addition to clarifying the role of catalysts, oxygen, light, and ultraviolet light in the reaction, it is also necessary to understand the types of reaction intermediates and their roles in the reaction before explaining the reaction mechanism. 0 / BiVO4 photocatalytic reaction uses free radicals and superoxide radicals (·O2– ), photogenerated holes (h + ), hydroxyl radical (·OH), singlet oxygen ( 1 O2) and photogenerated electrons (e – ) quencher, and compare the changes in cinnamaldehyde conversion rate, benzaldehyde selectivity and benzaldehyde yield. The experimental results are shown in Tables 10, 11 and 12.

[0197] In BiVO4-Ar-2h and xBi 0 / BiVO4, the addition of TEMPO completely inhibited the reaction, indicating that the 0 In the photocatalytic reaction of / BiVO4, free radicals are the key intermediates controlling the reaction. – , OH and 1 After adding the three most common oxygen species quenchers, O2, the reaction changes were different. After adding the three oxygen species quenchers BQ, FFA and TBA, the conversion rate of cinnamaldehyde decreased by more than 40%. 1 The O2 quencher FFA has the largest drop (all over 60%, the highest close to 70%), indicating that both in BiVO4-Ar-2h and xBi 0 / BiVO4 catalyzed 1 O2 is the main oxygen species that causes cinnamaldehyde to oxidize. – The effect of quenching agent on the conversion of cinnamaldehyde is second only to 1 O2, but xBi 0 / BiVO4 decreased more than BiVO4-Ar-2h, which indicates that loading single substance Bi will increase the amount of ·O2 generated in the reaction system to a certain extent. – The oxidizing power of ·OH is second only to that of elemental fluorine, and the stronger the oxidizing power, the lower the selectivity in the oxidation reaction. Therefore, the role played by ·OH in the reaction of catalyzing the selective oxidation of cinnamaldehyde by oxygen to prepare benzaldehyde is similar to 1 O2 and O2 – After adding TBA, the difference between 0 / BiVO4 catalyzed benzaldehyde selectivity showed a certain degree of improvement. 0 / BiVO4, the selectivity of benzaldehyde increased by 30%. This not only shows that ·OH is the main oxidant of the side reaction, but also shows that xBi loaded with Bi 0 / BiVO4 can effectively inhibit the generation of ·OH in the oxidation of cinnamaldehyde. 0 / BiVO4 can effectively eliminate the negative impact of trace water generated during oxidation reaction. 1 O2 and O2– After the quencher was quenched, the effect on the selectivity of benzaldehyde was significantly different. Adding BQ to inhibit the generation of ·O2 in the reaction system – , the selectivity of benzaldehyde decreased slightly. – It is another major oxygen species involved in the main reaction, but its role in the main reaction is weaker than 1 O2. Join FFA 1 After O2 inhibition, the selectivity of benzaldehyde was only less than 45% of the blank value. Since the data in Tables 10, 11, and 12 are the data of the 8th hour of reaction, it cannot be said that the inhibition of benzaldehyde during the entire reaction process 1 The trend of selectivity change after O2. Fig.26 The data show that xBi loaded with elemental Bi 0 The high efficiency of BiVO4 in the selective oxidation of cinnamaldehyde to benzaldehyde is entirely due to 1 The main reaction is caused by O2. 1 O2 makes benzaldehyde selectively react with Fig.21 The values ​​in b after 2 h under BiVO4-Ar-2h catalysis are comparable.

[0198] Since the reaction substrate cinnamaldehyde captures electrons to undergo a reduction reaction, the electrons do not directly participate in the oxidative cleavage reaction of the carbon-carbon double bond, but they will affect the main reaction. – Therefore, the addition of AgNO3 blocks the oxygen molecules from capturing photogenerated electrons to generate O2 – reaction, but does not affect the generation of light energy 1 O2. Therefore, the cinnamaldehyde conversion showed the largest decrease in the quenching experiment, but the change in benzaldehyde selectivity was much smaller. + The effect of the addition of inhibitors on the reaction is similar to that of electrons in terms of conversion, but the decrease in benzaldehyde selectivity is second only to 1 O2 inhibitor. This means that h + Participate in the main reaction of generating benzaldehyde. + It can accept electrons, so the reaction substrate cinnamaldehyde can react with the electron-rich region of the carbon-carbon double bond to form the catalyst surface. + Combined, a reaction occurs in which the carbon-carbon double bond is broken to generate benzaldehyde.

[0199] Table 10 Conversion results of quenching experiment of cinnamaldehyde oxidation

[0200]

[0201]

[0202] Table 11 Selectivity results of quenching experiments of cinnamaldehyde oxidation

[0203]

[0204] Table 12 Yield results of quenching experiment of cinnamaldehyde oxidation

[0205]

[0206] 4.3.3 Using TEMP and DMPO as spin labels, EPR was used to detect BiVO4-Ar-2h and xBi 0 / BiVO4 under light 1 O2 and O2 – The signal is shown in Fig.25 .

[0207] Before loading single element Bi, BiVO4-Ar-2h has no O2 under light care – signal, but it has considerable strength 1 O2 signal( Fig.25 a). This shows that BiVO4-Ar-2h itself has the characteristics of a photosensitizer. When loaded with elemental Bi, as the Bi loading amount increases, 1 The O2 signal strength increased by about 18% at most; however, the more obvious change occurred in the O2 – Signal Fig.25 b. When loaded with elemental Bi, O2 – The signal is generated from nothing and gradually increases. 0 / The CB position of BiVO4 satisfies the reduction of O2 to ·O2 – The potential of NHE is –0.33eV, but in fact, when there is no single substance Bi, BiVO4 absorbs light and only transfers energy to the oxygen molecules adsorbed on the catalyst surface, which excites their outer electrons and generates 1 O2. Only when the surface of BiVO4 is loaded with elemental Bi, can xBi 0 The presence of BiVO4 can make its own electrons have a forward channel, so after light exposure, it can produce ·O2 – That is, after the catalyst absorbs light energy, the energy has another way to be transferred, making xBi 0 / BiVO4 retains the properties of a photosensitizer and acquires another property of generating photogenerated electrons. This indicates that xBi 0 / BiVO4 is a "bifunctional" photocatalyst.

[0208] 4.3.4 O2 – and 1 Complete data of the O2 quenching experiment process ( Fig.26) and can better explain xBi 0 / The influence of BiVO4 “bifunctional” catalysis on the reaction

[0209] Fig.26 b is the addition of BQ quenching O2 – Later 1 The selectivity data of benzaldehyde in the reaction under O2 oxidation. The selectivity remained basically unchanged in the first 10 hours of the reaction; moreover, the effect of the loaded elemental Bi on the reaction selectivity was small. Fig.26 e, add FFA to quench 1 After O2, the benzaldehyde selectivity gradually increased with time, and the benzaldehyde selectivity after Bi loading was much better than that of BiVO4-Ar-2h. 1 O2 and O2 – There are also obvious differences in their roles in the reactions.

[0210] First, in 1 Cinnamaldehyde conversion rate under O2 oxidation ( Fig.26 a) From the beginning of the reaction, it is higher than in O2 – Oxidation ( Fig.26 d) High. 1 Under O2 oxidation, the conversion rate of cinnamaldehyde increased faster than that of the latter during the 10-hour reaction period. 0 The photosensitizer property in BiVO4's "dual function" is the original property of BiVO4, which makes xBi 0 / BiVO4 is fast in the reaction: it enters the high-efficiency catalytic state quickly (i.e., the reaction has high benzaldehyde selectivity and cinnamaldehyde conversion rate at the beginning) and the cinnamaldehyde conversion rate increases rapidly. 0 / BiVO4 brings the characteristics of generating photogenerated electrons, making xBi 0 / BiVO4 has the ability to generate ·O2 – The ability of O2 – The presence of not only increases the conversion rate of cinnamaldehyde by more than 2 times, but also gradually increases the selectivity of benzaldehyde. The effect on selectivity can offset the deactivation of the catalyst during the reaction, making the catalyst have another "long" feature, that is, maintaining high catalytic activity and long life.

[0211] 4.3.5 Effect of Bi loading on the oxygen molecule adsorption capacity of BiVO4

[0212] According to BiVO4-Ar-2h and xBi 0 / O2-TPD data of BiVO4( Fig. 27 ), the number of oxygen molecules physically adsorbed on its surface increased significantly after loading single substance Bi.0 / BiVO4's physically adsorbed oxygen molecule desorption signal intensity is higher than other xBi 0 / BiVO4 is more than twice that of BiVO4 and about 10 times that of BiVO4-Ar-2h. With such a high oxygen adsorption capacity, xBi 0 / BiVO4 is another important reason why the photocatalytic properties are significantly improved.

[0213] 4.3.6xBi 0 Mechanism of selective oxidation of cinnamaldehyde to benzaldehyde by photocatalytic oxygen in BiVO4

[0214] According to the above characterization and analysis, xBi 0 The mechanism of selective oxidation of carbon-carbon double bonds in cinnamaldehyde by photocatalytic oxygen from BiVO4 to prepare benzaldehyde was proposed, such as Fig.28 As shown. xBi loaded with Bi 0 / BiVO4 absorbs a large number of oxygen molecules on its surface. When exposed to light, the original photosensitizer properties of BiVO4 absorb light energy and quickly transfer the energy to the oxygen molecules adsorbed on the surface, stimulating the outer electrons of the oxygen molecules to generate 1 O2. The loaded Bi easily absorbs oxygen molecules and also absorbs oxygen in the carbonyl group of cinnamaldehyde, causing cinnamaldehyde to undergo hydroxyaldehyde tautomerism to form a carbon cation (I) at the β-carbon of the carbonyl group (the carbon atom connected to the phenyl group). 1 O2 will quickly attack I to generate intermediate II, which will then cyclize to generate a four-membered ring intermediate III. Finally, intermediate III will open the ring to obtain benzaldehyde. 0 / BiVO4 has the characteristic of generating photogenerated electrons. The generated photogenerated electrons can be captured by oxygen molecules adsorbed on the surface. – , and xBi 0 As photogenerated electrons are generated on the surface of / BiVO4, holes are generated. The holes can obtain an electron from the carbon-carbon double bond of cinnamaldehyde to generate free radical intermediates (IV and V), while cinnamaldehyde is adsorbed on the catalyst surface. Then, the single-electron·O2 – Combined with the carbon radicals of IV and V to give intermediates VIa and VIb. Next, the lone pair of electrons of the terminal oxygen in VIa and VIb attack the carbon cation, also cyclizing to give intermediate III, and ring-opening cleavage to generate benzaldehyde.

[0215] Example 5

[0216] Bismuth vanadate xBi supported by metal bismuth 0 / BiVO4 preparation method, comprising the following steps:

[0217] Step 1: Weigh bismuth nitrate pentahydrate and ammonium metavanadate according to a molar ratio of bismuth nitrate pentahydrate to ammonium metavanadate of 1:1+x, wherein x=0.1, x=0.15, x=0.25, x=0.3, x=0.35, x=0.45, x=0.5, x=0.55, x=0.65, x=0.7 or x=0.75; Step 2: Dissolve the bismuth nitrate pentahydrate weighed in Step 1 in ethylene glycol, and the solution is recorded as solution A; the bismuth nitrate pentahydrate and ammonium metavanadate in solution A are mixed. The mass volume ratio of the solvent w / v = 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5%; Step 3: dissolve the ammonium metavanadate weighed in Step 1 in deionized water, and the solution is recorded as solution B; the mass volume ratio of ammonium metavanadate to solvent in solution B is 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5%; Step 4: fully mix solution A and solution B, add ammonia water to adjust the solution pH to 6-8, and continue to stir and mix; Step 5: pour In the polytetrafluoroethylene liner of the autoclave, place the autoclave at 140, 145, 150, 153, 155, 158, 160, 163, 165, 168, 170, 175 or 180°C and keep warm for 6, 8, 10, 12, 14, 16, 18, 20, 22 or 24 hours; Step 6: Filter the product, wash it three times with anhydrous ethanol and deionized water respectively, then put it in a vacuum drying oven and dry it at 40, 45, 50, 55, 6 0, 65, 70, 75, or 80 ° C for 6, 8, 10, 12, 14, 16, 18, 20, 22 or 24h; Step 7: The dried product is calcined at 350, 380, 400, 425, 450, 475, 500, 525, 550, 575 or 600 ° C under argon protection for 2, 3, 4, 5 or 6h to obtain the product, and the products obtained at each x value in Step 1 are bismuth vanadate supported by metal bismuth 0.1Bi 0 / BiVO4, 0.15Bi 0 / BiVO4, 0.25Bi 0 / BiVO4, 0.3Bi 0 / BiVO4, 0.35Bi 0 / BiVO4, 0.45Bi 0 / BiVO4, 0.5Bi 0 / BiVO4, 0.55Bi 0 / BiVO4, 0.65Bi 0 / BiVO4, 0.7Bi 0 / BiVO4, 0.75Bi 0 / BiVO4.

[0218] Example 6

[0219] In this embodiment, bismuth nitrate pentahydrate and ammonium metavanadate are weighed according to a molar ratio of bismuth nitrate pentahydrate to ammonium metavanadate of 1:1, and the remaining steps are the same as those in Example 5 to obtain bismuth vanadate BiVO4-OVs containing oxygen vacancies.

[0220] Example 7

[0221] A method for preparing benzaldehyde, using cinnamaldehyde as a raw material, and using bismuth vanadate BiVO4-OVs containing oxygen vacancies or bismuth vanadate xBi supported by metal bismuth 0 / BiVO4 is used as a catalyst to catalyze oxygen oxidation of cinnamaldehyde under light conditions. The catalyst is added at 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, 7.0 or 7.5% of the mass of cinnamaldehyde. Cinnamaldehyde is dissolved in a solvent at a molar volume concentration of 0.1, 0.2, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9 or 1 mol / L. The solvent is acetonitrile, alcohol, ether, benzene or chloroform. The light condition is a xenon lamp irradiation light power density of 200, 250, 300, 350, 400, 450, 500, 550 or 600mw / cm 2 The photocatalytic reaction time is 2, 4, 6, 8, 9, 10, 11 or 12 hours.

Claims

1. A bismuth vanadate containing oxygen vacancies BiVO4-OVs or bismuth vanadate loaded with metal bismuth xBi 0 / BiVO4 preparation method, characterized in that, The following steps are involved: Step 1: Weigh bismuth nitrate pentahydrate and ammonium metavanadate according to a molar ratio of bismuth nitrate pentahydrate to ammonium metavanadate of 1:1+x, wherein 0≤x≤0.8; Step 2: dissolve the bismuth nitrate pentahydrate weighed in Step 1 in solvent A, and the solution is recorded as solution A; Step 3: dissolve the ammonium metavanadate weighed in Step 1 in solvent B, and the solution is recorded as solution B; Step 4: Mix solution A and solution B thoroughly, adjust the pH of the solution to 6-8, and continue stirring to mix; Step 5: Pour into the polytetrafluoroethylene lining of the autoclave, place the autoclave in an environment of 140-180°C, and keep warm for 6-24 hours; Step 6: Filter out the product, then wash and dry; Step 7: Calcine the dried product at 350-600°C for 2-6h under argon protection to obtain the product. When x=0 in Step 1, the product is bismuth vanadate BiVO4-OVs containing oxygen vacancies; when x>0 in Step 1, the product is bismuth vanadate xBi supported by metal bismuth. 0 / BiVO4.

2. The preparation method according to claim 1, characterized in that: In Step 2, the mass volume ratio of bismuth nitrate pentahydrate to the solvent in solution A is w / v=1-5%, and the solvent A for dissolving bismuth nitrate pentahydrate is ethylene glycol; in Step 3, the mass volume ratio of ammonium metavanadate to the solvent in solution B is w / v=1-5%, and the solvent B for dissolving ammonium metavanadate is deionized water.

3. The preparation method according to claim 1, characterized in that: In Step 4, the pH is adjusted by adding ammonia water.

4. The preparation method according to claim 1, characterized in that: In Step 6, wash three times with anhydrous ethanol and deionized water respectively, then put into a vacuum drying oven and keep warm at 40-80°C for 6-24h.

5. A method for preparing benzaldehyde, characterized in that: Using cinnamaldehyde as raw material, bismuth vanadate BiVO4-OVs containing oxygen vacancies or bismuth vanadate xBi supported by metal bismuth 0 / BiVO4 is used as a catalyst to catalyze the oxidation of cinnamaldehyde by oxygen under light conditions.

6. The method for preparing benzaldehyde according to claim 5, characterized in that: The catalyst is added at 1.5-7.5% of the mass of cinnamaldehyde.

7. The method for preparing benzaldehyde according to claim 5, characterized in that: Cinnamaldehyde is dissolved in a solvent at a molar volume concentration of 0.1 to 1 mol / L.

8. The method for preparing benzaldehyde according to claim 5, characterized in that: The solvent is acetonitrile, alcohol, ether, benzene or chloroform.

9. The method for preparing benzaldehyde according to claim 5, characterized in that: The illumination condition is a xenon lamp with a light power density of 200 to 600 mw / cm 2 The photocatalytic reaction time is 2 to 12 hours.

10. The bismuth vanadate BiVO4-OVs containing oxygen vacancies or the bismuth vanadate xBi loaded with metal bismuth 0 Application of BiVO4 as catalyst in photocatalytic oxygen oxidation of cinnamaldehyde to prepare benzaldehyde.

Citation Information

Patent Citations

  • Production method for natural benzaldehyde

    CN101985414A

  • A cobalt / tubular graphite phase carbon nitride composite material and its preparation method and application

    CN114950518B

  • Process for preparing natural benzaldehyde

    CN1634837A

  • Process for directly producing natural benzaldehyde using cassia twig leaf and cassia bark as raw material

    CN1749231A

  • Preparation method of natural benzaldehyde

    CN1911891A

Cited By

  • Thiocyanide-modified Ag / BiVO4 and application of thiocyanide-modified Ag / BiVO4 in preparation of aminomethyl phosphoric acid through photocatalytic oxidation of glyphosate

    CN120132918A

  • Use of thiocyanide-modified Ag / BiVO4 and photocatalytic oxidation of glyphosate to prepare aminomethylphosphonic acid

    CN120132918B